2020
DOI: 10.1021/acsnano.0c03009
|View full text |Cite
|
Sign up to set email alerts
|

Acoustofluidic Scanning Nanoscope with High Resolution and Large Field of View

Abstract: Figure S1) magnified images of Blu-ray disc surface are taken by different microscope objective and SEM; (Figures S2) analysis of super-resolution effects in different materials and sizes of microparticles; (Figures S3) simulation results of a 2 μm PS bead along two orthogonal directions with FDTD method; (Figure S4) Ge nanoparticles imaging through a PS-20 microsphere; (Figure S5) schematic explanation of reflection and transmission light illuminations; (Figure S6) comparison of optical resolutions of 800 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…Microlens‐based imaging can observe subcellular structures and adenoviruses, [ 28 , 29 , 30 ] as well as perform super‐resolution imaging on nonbiological samples such as semiconductor wafer patterns [ 31 , 32 , 33 , 34 , 35 ] and nanostructures. [ 36 , 37 , 38 ] When a single microlens is used for imaging, the imaging field of view (FOV) is limited by the size of the microsphere. To address this issue, microsphere scanning imaging can be achieved through the use of chemical driving, [ 39 ] acoustic fluids, [ 36 ] and optical tweezers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microlens‐based imaging can observe subcellular structures and adenoviruses, [ 28 , 29 , 30 ] as well as perform super‐resolution imaging on nonbiological samples such as semiconductor wafer patterns [ 31 , 32 , 33 , 34 , 35 ] and nanostructures. [ 36 , 37 , 38 ] When a single microlens is used for imaging, the imaging field of view (FOV) is limited by the size of the microsphere. To address this issue, microsphere scanning imaging can be achieved through the use of chemical driving, [ 39 ] acoustic fluids, [ 36 ] and optical tweezers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36 , 37 , 38 ] When a single microlens is used for imaging, the imaging field of view (FOV) is limited by the size of the microsphere. To address this issue, microsphere scanning imaging can be achieved through the use of chemical driving, [ 39 ] acoustic fluids, [ 36 ] and optical tweezers. [ 40 , 41 , 42 ] In addition, a 3D translation stage can be used to precisely control the microsphere integrated within a conventional microscope objective lens, [ 43 , 44 ] a capillary glass tube, [ 45 , 46 ] a tungsten probe, [ 47 ] and an AFM probe.…”
Section: Introductionmentioning
confidence: 99%
“…The magnification and lateral resolution can be further improved by immersing As 2 S 3 microspheres in media with a lower refractive index (e.g., polydimethylsiloxane). In addition to conventional microscopes, As 2 S 3 microspheres can also be used in combination with other microscopic platforms (e.g., scanning laser confocal microscope, [37] acoustofluidic scanning microscope, [38] and white-light interferometry [39] ) to significantly improve their lateral [37,38] or axial [39] imaging performance. They can further be integrated with a mechanical scanning system (e.g., atomic force microscopy cantilever [36,40] ) or optically trapped [41] to precisely control the imaging position in liquid environments and greatly expand the FOV for super-resolution imaging of largearea specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, microlens arrays (MLAs) have attracted extensive attention due to their wide applications in various fields such as digital displays, [ 1–3 ] light‐emitting‐diodes (LEDs), [ 4,5,6,7 ] super‐resolution imaging, [ 8,9,10 ] and artificial compound eyes. [ 11,12,13 ] The demand of MLAs with precise shaping features has increased over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microlens arrays (MLAs) have attracted extensive attention due to their wide applications in various fields such as digital displays, [1][2][3] light-emitting-diodes (LEDs), [4,5,6,7] super-resolution imaging, [8,9,10] and artificial compound used to fabricate micro/nanolens arrays (M/NLAs). [13,28] Zhou et al reported that the diameters of the MLAs fabricated by E-jet printing decreased from 32.45 to 1.59 µm when the inner diameter of the nozzle decreased from 25 to 1 µm.…”
Section: Introductionmentioning
confidence: 99%